2022
DOI: 10.3390/su14105806
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Consumer Behavior toward Green Consumption

Abstract: The aim of this study was to determine the relationship between the attitudes and behaviors of the administrative staff of four Baku universities toward the consumption of environmentally friendly products. The study used 536 consumer questionnaires belonging to different socio-economic and demographic consumer groups. The survey evaluated the factors that affected purchasing decisions, purchase intentions, awareness, attitudes and behaviors toward green products of respondents living in an urban area. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 96 publications
0
20
0
3
Order By: Relevance
“…[ 46 , 47 ]. Education level slightly influenced what consumers’ think is important to be on labels; this is in disagreement with Zeynalova and Namazova, who instead states that a higher level of education leads to greater interest in the information on the label [ 48 ]. Only two significant differences were observed in the indication of packaging material and type of recycling collection, whereby the least educated people were found to be the least interested.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 , 47 ]. Education level slightly influenced what consumers’ think is important to be on labels; this is in disagreement with Zeynalova and Namazova, who instead states that a higher level of education leads to greater interest in the information on the label [ 48 ]. Only two significant differences were observed in the indication of packaging material and type of recycling collection, whereby the least educated people were found to be the least interested.…”
Section: Discussionmentioning
confidence: 99%
“…People's environmental sensitivity helps them have positive attitudes toward businesses' environmental practices (Jeong et al, 2014). While determining the traits of consumers who are sensitive to the environment and buy green products, demographics and personality traits along with attitudes are considered to be identifying factors (Zeynalova & Namazova, 2022). Kumar & Ghodeswar (2015) found that women, individuals with high income, those who are married, and those over 45 to behave responsibly toward the environment and tend to prefer green products.…”
Section: Green Product Buying Behavioursmentioning
confidence: 99%
“…Likewise, the call for future research on adopting green behavior through integrating internal and external factors (Sajeewanie et al, 2019); the inadequacy of information hindering green behavior (Guru & Ranchhod, 2005). However, Zeynalova and Namazova's (2022) research reported that green behavior varied by customers' level of education, income, and family size that overall customers tend to demonstrate partial sensitivity to environmental concerns. Hence, to address the calls for empirically supported evidence, the present study focused on determining the root causes and effects of environmental partners' normative roles in achieving green consumerism and its interactions with greenwashing perceptions.…”
Section: Introductionmentioning
confidence: 99%